Evaluation of the pelvic flor by introital ultrasound - Apaza Valencia, John (2016)
This review describes the use of introital ultrasound in the evaluation of the pelvic floor, as a complementary method in the clinical study of urinary incontinence and genital prolapse. Additionally, we discuss the advantage of proceedings and images with the linear transducer in the evaluation of the levator ani. This review aims to expand the scope of use of the ultrasound in the evaluation of the pelvic floor and to improve the obstetrician/gynecologist’s diagnostic ability in Urogynecology.